2021
DOI: 10.1002/hed.26733
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative near‐infrared autofluorescence imaging for hypocalcemia risk reduction after total thyroidectomy: Evidence from a meta‐analysis

Abstract: This meta‐analysis evaluates whether near‐infrared autofluorescence (NIRAF) imaging reduces the risk of hypocalcemia after total thyroidectomy. A systematic literature search in PubMed, EMBASE, Web of Science, and Cochrane Library for studies from June 2011 to January 2021 comparing total thyroidectomy with NIRAF and conventional surgery (naked eye). Six eligible studies involving 2180 patients were included. The prevalence of transient hypocalcemia was 8.11% (40/493) and 25.19% (425/1687) in the NIRAF and nak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Benmiloud et al (18) demonstrated that the use of the autofluorescence-detecting devices was associated with an increased mean number of identified PTGs, a reduced rate of parathyroid autotransplantation, and a significantly lower rate of immediate postoperative hypocalcemia (5.2% vs. 20.9%). A meta-analysis of six eligible studies with a total of 2180 patients showed that NIRAF imaging reduces the risk of transient hypocalcemia and may lower the rate of permanent hypocalcemia (19). The prevalence of transient hypocalcemia was 8.11% (40/493) and 25.19% (425/1687) in the NIRAF and naked eye groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Benmiloud et al (18) demonstrated that the use of the autofluorescence-detecting devices was associated with an increased mean number of identified PTGs, a reduced rate of parathyroid autotransplantation, and a significantly lower rate of immediate postoperative hypocalcemia (5.2% vs. 20.9%). A meta-analysis of six eligible studies with a total of 2180 patients showed that NIRAF imaging reduces the risk of transient hypocalcemia and may lower the rate of permanent hypocalcemia (19). The prevalence of transient hypocalcemia was 8.11% (40/493) and 25.19% (425/1687) in the NIRAF and naked eye groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors included 6 studies involving 2180 patients. The prevalence of transient hypocalcemia was 8.11% in the NIR-AF group and 25.19% in the N-E group (p < 0.0001), while the prevalence of permanent hypocalcemia was 0% in the NIR-AF group and 2.19% in the N-E group (p = 0.05) [60].…”
Section: Identification Of Parathyroid Glands With Fluorescence Systemsmentioning
confidence: 86%
“…The recommended dose for PG visualization is 0.2-0.5 mg/kg, which may be repeated as required without exceeding the maximal daily dose of 5 mg/kg [56][57][58]. Both techniques have shown promising results in several studies in the literature [46][47][48]54,59,60].…”
Section: Identification Of Parathyroid Glands With Fluorescence Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, unfortunately only a few studies have demonstrated a direct correlation between visualization and glandular perfusion and a reduction in hypoparathyroidism [30], which is in any case limited to the temporary but not definitive form. Moreover, none of the prevention methods adopted seem to be able to reduce hypocalcaemia [42,[49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%